2019
DOI: 10.15666/aeer/1703_64576471
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Elite Tomato Lines Comprising Leaf Curl Virus Resistance Genes

Abstract: Tomato leaf curl virus is a serious threat to an autumn-winter crop of tomato in North India, causing yield losses up to 90-100%. Therefore, nine resistant and one susceptible line (Punjab Chhuhara) of tomato were crossed in half-diallel fashion to develop 45 F 1 hybrids. Parents and their hybrids were evaluated for yield and quality traits under natural epiphytotic field conditions. There were extensive differences in the performance of parental lines carrying similar and different resistance genes (Ty-X). Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The magnitude of heterosis depends on the genetic diversity existing between the parents. In a crop like a tomato, where there are evidences for polygenic action determining the yield, and the yield components the choice of parents must be based on refined biometrical techniques (Vijeth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of heterosis depends on the genetic diversity existing between the parents. In a crop like a tomato, where there are evidences for polygenic action determining the yield, and the yield components the choice of parents must be based on refined biometrical techniques (Vijeth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ANOVA on the half diallelic showed a significant effect on all characters, indicating that the half diallelic concept was effective. The effectiveness of using the half diallelic mating design was also reported by Pandiarana et al (2015); Kumar and Paliwal (2016); Kaushik and Dhaliwal (2018);and Vijeth et al (2019) on tomatoes, Boyaci et al (2020) and Datta et al (2021) on eggplant, andDianga et al (2020) on rice. Based on these studies, an in-depth analysis of genetic parameters, namely heritability, gene action, and combining ability, can be determined.…”
Section: Evaluation Of Half Diallelmentioning
confidence: 55%
“…It was shown that the two hybrids R1×Y53 and R1×F3 gave significant heterozygosity to the average fruit weight on the basis of the best parents, while the hybrid Y53×D4 gave positive hybrid vigor in the direction Desired number of fruits, plant yield and total yield based on the best of the parents. Confirmed [12] in a study conducted at Punjab Agricultural University when they studied ten pure lines of tomato and forty-five individual crosses, the hybrid vigor measured on the basis of the best parents was significant and desirable in hybrids CLN138B × PVB-1, CLN138A × CLN154 and CLN1138B × 2123C, for the average weight of the fruit The plant yield, in general, the hybrids recorded an increase in the percentage of the total yield, the average weight of the fruits and the total acidity of the fruits compared to the pure lines. as proven [13] Through the study to evaluate 30 hybrids produced by complete cross-crossing, most of the hybrids gave high hybrid vigor to most important traits such as yield traits.…”
Section: Hybrid Vigormentioning
confidence: 91%